Analysis of stride parameters and running velocity at indoor 400 m running - Silinskas, V.; Grunovas, A.; Stanislovaitiene, J. (Baltic Journal of Sport and Health Sciences, 2015)
Background. 400 m race is one of most difficult and complex events in athletics. In order to achieve good results in the distance an athlete must have not only good velocity characteristics, but also be able to tactically correctly allocate them, i.e. depending on their total and special endurance level be able to distribute efforts in the entire range, select the optimum running velocity for the start and keep it until the finish. Research aim was to analyse the choice of running tactics and change of stride parameters and running velocity of the best Lithuanian 400 m runners during a running indoor contest. Methods. The study was conducted during Lithuanian Indoor Championship. The best 15 runners of 400 meters were investigated. The runners were filmed by Digital cameras from the side at a distance of 90, 190, 290 and 390 meters. We analysed stride kinematic parameters (duration of support and flight, stride length, stride frequency) and the running velocity. Results. The maximum decrease of the stride length and running velocity were observed between 190 and 290 m where the stride length decreased from 2.22 ± 0.03 to 2.08 ± 0.03 m and running velocity from 8.18 ± 013 to 7.36 ± 0.07 m/s. In the first distance range, i.e. 90 m, the stride frequency was 3.83 ± 0.05 Hz. Later it gradually decreased to 3.46 ± 0.05 Hz in 390 meters. Duration of support at 90 m was 0.119 ± 0.001 s and till 290 m it become longer, later it was almost unchanging. Time of flight phase changed insignificantly over the entire distance. Conclusion. It was found that athletes` choice of running tactics depended not only on their preparation type (sprint or endurance), but also on the conditions in which the athlete starts (indoor or outdoor), as well as on the number of the track in which the athlete starts. The maximum change of running velocity and stride length during the indoor running was observed in the second half of the range, while the stride frequency decreased gradually during the entire range. Change of support time had greater impact for stride frequency than change of flight time.